Pengaruh Solvabilitas dan Sales Growth Terhadap Kesulitan Keuangan dengan Profitabilitas Sebagai Variabel Moderasi - Nabilah Khamaliyah Effendi; Anwar Hariyono (Universitas Muhammadiyah Gresik, 2022)
This study aims to examine the effect of solvability and sales growth on financial distress with profitability as a moderating variable in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The population used is manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) in 2017-2019. Sampling using purposive sampling method and obtained as many as 39 companies that meet the criteria. Hypothesis testing in this study using descriptive analysis method with the analysis tool Moderating Regression Analysis (MRA) with the help of the SPSS application. The independent variables used in this study are solvability and sales growth, financial distress as the dependent variable and profitability as a moderating variable. Based on the research results, it is known that solvability has a significant effect on financial distress and sales growth has no effect on financial distress and profitability is not able to moderate the effect of solvability on financial distress and profitability is able to moderate the effect of sales growth on financial distress.